Serine Metabolism in Health and Disease and as a Conditionally Essential Amino Acid - Holeček, Milan (Nutrients, 2022)
L-serine plays an essential role in a broad range of cellular functions including protein synthesis, neurotransmission, and folate and methionine cycles and synthesis of sphingolipids, phospholipids, and sulphur containing amino acids. A hydroxyl side-chain of L-serine contributes to polarity of proteins, and serves as a primary site for binding a phosphate group to regulate protein function. D-serine, its D-isoform, has a unique role. Recent studies indicate increased requirements for L-serine and its potential therapeutic use in some diseases. L-serine deficiency is associated with impaired function of the nervous system, primarily due to abnormal metabolism of phospholipids and sphingolipids, particularly increased synthesis of deoxysphingolipids. Therapeutic benefits of L-serine have been reported in primary disorders of serine metabolism, diabetic neuropathy, hyperhomocysteinemia, and amyotrophic lateral sclerosis. Use of L-serine and its metabolic products, specifically D-serine and phosphatidylserine, has been investigated for the therapy of renal diseases, central nervous system injury, and in a wide range of neurological and psychiatric disorders. It is concluded that there are disorders in which humans cannot synthesize L-serine in sufficient quantities, that L-serine is effective in therapy of disorders associated with its deficiency, and that L-serine should be classified as a "conditionally essential" amino acid.
Keywords: sfingolipidy; Amino Acids, Essential; Serine; serin; fosfolipidy; lidé; esenciální aminokyseliny; Amino Acid Metabolism, Inborn Errors; vrozené poruchy metabolismu aminokyselin; Sphingolipids; Phospholipids; Humans